The clinical application of V-Y advanced flap pedicled with freestyle perforator flap for repairing small range defects in the anterior knee region - Qian, Da; Jin, Lijie; Huang, Guoxin; Dai, Ping; Li, Dong; Lu, Hui; Xu, Ming; Wang, Ke; Zhong, Xian; Xu, Xiaochen; Zhang, Jianchao; Yu, Bin (Frontiers in Surgery, 2024)
Introduction This study aims to investigate the clinical efficacy of V-Y advanced flap pedicled with freestyle perforator flap for repairing small range defects in the anterior knee region. Methods 8 patients with skin and soft tissue defect/necrosis in the anterior knee area admitted to the Changshu No.1 People's Hospital from January 2021 to January 2022 were selected, with a defect range of 4 cm × 3 cm–9 cm × 6 cm, designed a V-Y advanced flap pedicled with freestyle perforator flap to repair the wound in the anterior knee area. Adjust the size and position of the flap according to the number and position of perforating branches found during the surgery, with a cutting area of 6 cm × 5 cm–14 cm × 10 cm and the supply area was directly pulled and sutured. Results 4 patients were repaired by flaps pedicled with 2 perforating branches, 2 patients were repaired by flaps pedicled with 1 perforating branch and 2 patients were repaired by flaps pedicled with 3 perforating branches. 4 patients were repaired by flaps pedicled with 2 perforating branches, 2 patients were repaired by flaps pedicled with 1 perforating branch and 2 patients were repaired by flaps pedicled with 3 perforating branches. All flaps survived and following up for 6-15 months, the blood supply, appearance, and color of the flap were satisfactory, and the functions of knee joint flexion and extension were well preserved. Discussion The V-Y advancement flap pedicled with freestyle perforator flap has the advantages of reliable blood supply, simple surgical operation, texture and thickness similar to the skin of the anterior knee area, and direct suture of the donor area. It is a perforator flap with good repair effect for small scale defects in the anterior knee area.